2017
DOI: 10.1039/c7cc04090c
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient chemoenzymatic synthesis and facile purification of α-Gal pentasaccharyl ceramide Galα3nLc4βCer

Abstract: A highly efficient chemoenzymatic method for synthesizing glycosphingolipids using α-Gal pentasaccharyl ceramide as an example is reported here. Enzymatic extension of chemically synthesized lactosyl sphingosine using efficient sequential one-pot multienzyme (OPME) reactions allowed glycosylation be carried out in aqueous solution. Facile C18 cartridge-based quick (<30 minutes) purification proctols were established using minimal amounts of green solvents (CH3CN and H2O). Simple acylation in the last step led … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 51 publications
1
34
0
Order By: Relevance
“…Solution-phase synthesis with a substrate bound to water-soluble [224] or thermo-responsive polymers [225], fluorous- [217,226,227,228,229,230,231,232,233,234,235,236], ion exchange [237], or lipid-like tags [238] has attracted much interest since it can bypass compatibility issues between enzymes and solid carriers. The main disadvantage of solution-phase assembly of oligosaccharides catalyzed by glycosyltransferases is the low catalytic efficiency and affinity for the substrates due to different steric and stereoelectronic properties induced by the substrate-bound tag.…”
Section: Reactor Engineering For (Non)-leloir Glycosyltransferasesmentioning
confidence: 99%
“…Solution-phase synthesis with a substrate bound to water-soluble [224] or thermo-responsive polymers [225], fluorous- [217,226,227,228,229,230,231,232,233,234,235,236], ion exchange [237], or lipid-like tags [238] has attracted much interest since it can bypass compatibility issues between enzymes and solid carriers. The main disadvantage of solution-phase assembly of oligosaccharides catalyzed by glycosyltransferases is the low catalytic efficiency and affinity for the substrates due to different steric and stereoelectronic properties induced by the substrate-bound tag.…”
Section: Reactor Engineering For (Non)-leloir Glycosyltransferasesmentioning
confidence: 99%
“…Recently, we showed that α-Gal pentasaccharyl ceramide, a neutral glycosphingolipid, can be chemoenzymatically synthesized from water soluble lactosyl sphingosine (LacβSph) with simple C18-cartridge solid phase extraction (SPE) purification procedures followed by acylation. 23 Herein, we develop high-yield streamlined chemoenzymatic processes for total synthesis of synthetically challenging complex gangliosides. A 13-gram-scale synthetic procedure is established for producing LacβSph from commercially available inexpensive lactose and phytosphingosine.…”
mentioning
confidence: 99%
“…To obtain target gangliosides, LacβSph ( 5 ) 23 was prepared from lactose and phytosphingosine in a 13-gram scale to demonstrate the efficiency of the streamlined chemical synthetic procedure and to provide a sufficient amount of starting material for glycosphingolipid synthesis. The synthesis was achieved in 12 steps in an overall 40% yield (see ESI).…”
mentioning
confidence: 99%
“…The sphingosine component facilitated the facile C18cartridge-based purification processes (Figure 14). Ganglio-and neolacto-series glycosphingolipids have been successfully obtained using the strategy [67,68]. Compared to en bloc transfer of oligosaccharides from chemoenzymatically synthesized oligosaccharyl fluorides for the synthesis of glycosphingolipids and glycosphingosines containing a sphingoid base or its derivative using endoglycoceramidase mutants (endoglycoceramidase glycosynthase) [69,70], the OPME glycosylation of LacβSph strategy is more flexible in accessing a more diverse array of products and also provides an easier C18 cartridgepurification process.…”
Section: Chemoenzymatic Synthesis Of Glycolipids With Facile Purificamentioning
confidence: 99%